Effect of high-frequency repetitive transcranial magnetic stimulation (rTMS) in patients with comorbid panic disorder and major depression. (August 2018) - Kumar, Saurabh; Singh, Swarndeep; Parmar, Arpit; Verma, Rohit; Kumar, Nand
Objective: To explore the role of dorsolateral prefrontal cortex (DLPFC) stimulation in the treatment of panic disorder with comorbid depression. Methods: The present study reports findings from retrospective analysis of 13 treatment-resistant patients diagnosed with comorbid panic disorder and depression, given 20 sessions of high-frequency transcranial magnetic stimulation (rTMS) over left-DLPFC over a period of 1 month. Results: There was a significant reduction in both the panic and depressive symptom severity, assessed by applying Panic Disorder Severity Scale (PDSS) and Hamilton Depression Rating Scale (HDRS) at baseline and after 20 sessions of rTMS. There was a 38% and 40% reduction of PDSS and HDRS scores, respectively, in the sample. The changes in PDSS and HDRS scores were not significantly correlated (ρ = –0.103, p  = 0.737). Conclusions: High-frequency rTMS delivered at left-DLPFC may have a potential role in treatment of comorbid panic disorder and depression. Future studies done on a larger sample in a controlled environment are required to establish its role.